W kwestii wymiaru medialno-metodycznego historii rodziny w nauczaniu historii w szkole podstawowej - Štěpánek, Kamil (Karkonoska Państwowa Szkoła Wyższa, 2011)
The text of the contribution is inspired by relationships and issues arising from communication among parents, children, grandparents and grandchildren. It ensues from such terms as generation crisis, cohesion, cultivation of common values or family topics. It deals with family history captured in a family amateur movie, which is an appropriate media of alternative school and out-of-school pupils' activities.Within its framework the pupils can become aware of their own roots and evolution of their family histories, or how their histories were influenced by „the great history”. The presentation methodology of the summary of these pupils' explorations of private family materials used in history lessons forms an inseparable part.
Keywords: historia; edukacja; rodzina; metodologia; film; szkoła podstawowa